Three-dimensional conformal radiation for esophageal squamous cell carcinoma with involved-field irradiation may deliver considerable doses of incidental nodal irradiation - Ji, Kai (BioMed Central, 2012)
BACKGROUND: To quantify the incidental irradiation dose to esophageal lymph node stations when irradiating T1-4N0M0 thoracic esophageal squamous cell carcinoma (ESCC) patients with a dose of 60 Gy/30f. METHODS: Thirty-nine patients with medically inoperable T1–4N0M0 thoracic ESCC were treated with three-dimensional conformal radiation (3DCRT) with involved-field radiation (IFI). The conformal clinical target volume (CTV) was re-created using a 3-cm margin in the proximal and distal direction beyond the barium esophagogram, endoscopic examination and CT scan defined the gross tumor volume (GTV) and a 0.5-cm margin in the lateral and anteroposterior directions of the CT scan-defined GTV. The PTV encompassed 1-cm proximal and distal margins and 0.5-cm radial margin based on the CTV. Nodal regions were delineated using the Japanese Society for Esophageal Diseases (JSED) guidelines and an EORTC-ROG expert opinion. The equivalent uniform dose (EUD) and other dosimetric parameters were calculated for each nodal station. Nodal regions with a metastasis rate greater than 5% were considered a high-risk lymph node subgroup. RESULTS: Under a 60 Gy dosage, the median D(mean) and EUD was greater than 40 Gy in most high-risk nodal regions except for regions of 104, 106tb-R in upper-thoracic ESCC and 101, 104-R, 105, 106rec-L, 2, 3&7 in middle-thoracic ESCC and 107, 3&7 in lower-thoracic ESCC. In the regions with an EUD less than 40Gy, most incidental irradiation doses were significantly associated with esophageal tumor length and location. CONCLUSIONS: Lymph node stations near ESCC receive considerable incidental irradiation doses with involved-field irradiation that may contribute to the elimination of subclinical lesions.